Unveiling the Diversity of Periphytic Cyanobacteria (Cyanophyceae) from Tropical Mangroves in Penang, Malaysia - Nur Afiqah Abdul Rahim; Faradina Merican Mohd Sidik Merican; Ranina Radzi; Wan Maznah Wan Omar; Siti Azizah Mohd Nor; Paul Broady; Peter Convey (Tropical Life Sciences Research, 2023)
Cyanobacteria are one of the most important groups of photoautotrophic organisms, contributing to carbon and nitrogen fixation in mangroves worldwide. They also play an important role in soil retention and stabilisation and contribute to high plant productivity through their secretion of plant growth-promoting substances. However, their diversity and distribution in Malaysian mangrove ecosystems have yet to be studied in detail, despite Malaysia hosting a significant element of remaining mangroves globally. In a floristic survey conducted in Penang, peninsular Malaysia, 33 morphospecies of periphytic cyanobacteria were identified and described for the first time from a mangrove ecosystem in Malaysia. Sixteen genera, comprising Aphanocapsa, Chroococcus, Chroococcidiopsis, Cyanobacterium, Desmonostoc, Geitlerinema, Leptolyngbya, Lyngbya, Microcystis, Myxosarcina, Oscillatoria, Phormidium, Pseudanabaena, Spirulina, Trichocoleus and Xenococcus, were obtained from field material growing on diverse natural and artificial substrata. Oscillatoriales was the dominant order with Phormidium the dominant genus at nine of the 15 sampling sites examined. Three of the morphospecies, Aphanocapsa cf. concharum, Xenococcus cf. pallidus and Oscillatoria pseudocurviceps, are rare and poorly known morphospecies worldwide. Chroococcus minutus, Phormidium uncinatum, P. amphigranulata, and some species of Oscillatoriales are considered as pollution indicator species. This study provides important baseline information for further investigation of the cyanobacterial microflora present in other mangrove areas around Malaysia. A complete checklist will enhance understanding of their ecological role and the potential for benefits arising from useful secondary metabolites or threats via toxin production to the ecosystem.